What drive investors to invest in socially responsible investment Sukuk? A pilot study / Mohamad Rozain Abbas, Nurhazrina Mat Rahim and Norli Ali - Abbas, Mohamad Rozain; Mat Rahim, Nurhazrina; Ali, Norli (2023)
Socially Responsible Investment (SRI) Sukuk has been around for almost a decade in Malaysia to promote funding for sustainable and responsible investment. Yet the issuance of SRI Sukuk remains limited and concentrates only on renewable energy projects. As the Sukuk is issued based on demand, it is crucial to identify the factors stimulating that demand. Theoretically, investors' attitudes towards the investment and the financing instrument, subjective norms, and moral intensity may influence such demand. Thus, this study intends to investigate the impact of attitude (AT), subjective norm (SN), and moral intensity (MI) on SRI Sukuk investors' intention (SII). It also adopted an online survey technique to collect 55 samples from fund managers of institutional investors.